L’interpellation entre immobilisation et mise en mouvement. Un genre dialogique et situé de l'activité - Jean-Paul Bernié (Corela)
This paper aims to show that interpellation cannot be reduced to monological acts or gestures, but makes up a didactic activity genre, within the framework of a co-activity basically dialogical. From this point of view, it affords various properties, particularly an indecisiveness of effects, which doesn’t allow any analysis excluding specific knowledges at stake, or without examination of situations or contexts. Seen from that angle, it makes up a precious observatory of the reorganization of higher psychical abilities under the effects of knowledge acquiring –particularly because it brings to light the forks proper to the apprenticeship courses. So, the analysis of the interpellation requires the widening of  the observed units, and a new approach of language, as shown in the activity theory.